PENGARUH GAYA KEPEMIMPINAN DIREKTIF, MOTIVASI DAN DISIPLIN TERHADAP KINERJA (Studi Pada Prajurit Markas Komando Pangkalan TNI Angkatan Laut Palu) - Supriady, Ferry (Katalogis, 2015)
The objectives of this research are: (1) to know and analyze effect directive leadership style, motivation and dicipline in simultaneously on perfomance; (2) to know and analyze effect directive leadership style on perfomance; (3) to know and analyze the effect of motivation on perfomance; (4) to know and analyze the effect of dicipline on perfomance. This research employs explanatory to investigate the relationship among variables involving 72 samples that have been determined using sencus method. The result show that: (1) directive mode of leadership, motivation and dicipline perform positive and significant effect on personnel’s perfomances at Indonesian Navy of Palu Naval Based; (2) directive mode of leadership perform positive and significant effect on personnel’s perfomances; (3) Motivation perform positive and significant effect on personnel’s performances (4) dicipline perform positive and significant effect on personel’s perfomances.